Rol docente y su incidencia en la enseñanza-aprendizaje de valores cívicos a los estudiantes de la escuela aurora Estrada y Ayala del cantón Babahoyo, provincia de los Ríos - Ramos Chávez, Katherine Liseth (2015)
Speaking of civic values, we can imagine standards of behavior or patriotism for our country. Many concepts that can make; but only one summarize and clarifies our doubts. Civic values are standards of behavior towards the homeland, their emblems and historical resources that compose it .Demonstrate good citizenship is not something one minute and nothing more; It is at all times, instantly or where we are, whether inside or outside the country. It's nice to see when soldiers carry the fervor and ardent desires to defend their homeland, when for a moment shed a tear and kiss the flag that identify him as a patriot. It's nice to see the students, bringing his hand to his chest and sonorous voice singing the hymn that one day led his nation to freedom. That's why the slogan "love life" is not only take care of ourselves, but; is loving the country, culture and other resources around us are natural and historical.